Tradition in Transition: Cultural Adaptation and Social Change in Contemporary Communities - Khoiriyah, Khoiriyah; Mendes, Clara; Chai, Napat (Yayasan Adra Karima Hubbi, 2026)
Background. In contemporary societies, cultural traditions face constant pressure from globalization, modernization, and social change. These forces often lead to the adaptation and transformation of cultural practices, creating a dynamic tension between tradition and progress. Understanding how communities navigate these transitions is critical for understanding the mechanisms of cultural preservation and transformation. Purpose. This study aims to examine the processes of cultural adaptation and social change in contemporary communities. By investigating how communities balance the preservation of traditions with the demands of modern life, the research seeks to shed light on the factors influencing cultural evolution and the impact of social change on traditional practices. Method. A qualitative research approach is employed, utilizing in-depth interviews and participant observation within several communities undergoing significant cultural transitions. Data is collected from various social groups, including older and younger generations, to explore differing perspectives on tradition and change. Results. The study finds that while traditional practices remain important, they are continually reinterpreted and adapted to align with modern values and lifestyles. Younger generations tend to prioritize aspects of tradition that align with global trends, while older generations emphasize the preservation of original practices. Conclusion. This research underscores the complexity of cultural adaptation and highlights the role of intergenerational dialogue in negotiating the tension between tradition and change.